Hubungan Terpaan Iklan Youtube dan Terpaan Influencer Marketing di Instagram pada Kampanye #EminaBeautyBestie dengan Keputusan Pembelian Rangkaian Produk Emina Bright Stuff Series - Tri Muriati Harahap, Anggi; Pradekso, Tandiyo; Pudjo Santosa, Hedi (Interaksi Online, 2021)
In promoting its newest series of skincare products, named Emina Bright Stuff Series, Emina launched a marketing communication strategy in the form of the #EminaBeautyBestie campaign over the past two years. Two forms of Integrated Marketing Communication run by Emina in campaigning for this product are by advertising on Youtube (Youtube Ads) and influencer marketing on Instagram. Behind the incessant marketing communication activities carried out by Emina, several national surveys showed that Emina Bright Stuff Products Series were not the choice of most consumers in determining skincare product purchasing decisions. This study aims to explain the correlation among Youtube ads exposure and influencer marketing exposure on Instagram of #EminaBeautyBestie campaign simultaneously with the purchase decision of the Emina Bright Stuff Product Series. This study uses a Cognitive Response Approach, with a sampling technique in the form of non-probability sampling. The sample consisted of 50 females, aged 15-25 years, and had been exposed to exposure to Youtube ads and influencer marketing on Instagram regarding #EminaBeautyBestie campaign in the last three months. The tests is carried out by using the Multiple Correlation technique. The results showed a significance value of 0.819, which means that there is no simultaneous significant relationship between Youtube ads exposure (X1) and influencer marketing exposure on Instagram (X2) of #EminaBeautyBestie campaign with the purchase decision of Emina Bright Stuff (Y) product series.